Quantitative angiographic assessment of aortic regurgitation post 11 different types of TAVI devices a multicentre pooled analysis of 2665 valves. (3rd October 2022) - Abdelshafy, M; Soliman, O; Kim, W; Ruck, A; Elkoumy, A; Elzomor, H; Wang, R; Tao, L; Garg, S; Mylotte, D; Onuma, Y; Serruys, P
Abstract: Background: Regurgitation following TAVR impacts all-cause mortality. So far, no quantitative comparison of regurgitation by the same core lab has been performed among the various commercially available transcatheter heart valves (THV) We aimed to compare quantitative angiographic aortic regurgitation (AR) of 11 different types of THVs. Method: This is a multicentre retrospective corelab pooled analysis of aortograms from 2704 consecutive patients treated with 11 different THV devices. Analysis was done by quantitative videodensitometric aortography (LVOT-AR), which is an objective, accurate, and reproducible tool for assessment of AR following TAVR. This method relies on time density changes in contrast medium after injection in the ascending aorta and its regurgitation (and subsequent density increase) in the LVOT. The ratio between the areas under the two-time density curves of these regions quantifies the AR in absolute percentage. The valves evaluated include ACURATE neo2 (n=120), Lotus (n=546), Myval (n=108), VitaFlow (n=105), Evolut PRO (n=95), SAPIEN 3 (n=397), Evolut R (n=295), SAPIEN XT (n=239), ACURATE neo (n=120), Venus-A (n=113) and CoreValve (n=532). Stratification of continuous variable regurgitation into categorical variables was performed according to the following pre-determined threshold criteria: 1) none/trace regurgitation (LVOT-AR<6%); 2) mild (6%≤ LVOT-AR ≤17%); and 3) moderate or severe (LVOT-AR >17%). Results: The addition of anti PVR sealing features to the new generations ACURATE neo2 THV proved to be effective in reduction the incidence of significant PVR In comparison with the first generation ACURATE neo. Myval, VitaFlow and Venus-A THVs are showing promising results. Although the incidence of moderate/severe AR has regressed over time with new generations of THVs, the incidence of mild AR is still prominent with all THVs still exhibiting mild AR with an incidence ranging between 30% and 50% with the exception of the Lotus valve that had an 19% incidence of mild AR Conclusion: ACURATE neo2 had the lowest severe/moderate percentage of AR showing significant improvements in comparison to ACURATE neo. Myval, VitaFlow and Venus-A are promising options in the THV armamentarium. These results should be confirmed in prospective randomized, head-to-head comparisons between THVs. Funding Acknowledgement: Type of funding sources: None.